Electricity prices in a mixed thermal and hydropower system - Michael Hoel (University of Oslo, Department of Economics, 2004)
When a monopolistic hydro producer interacts with a competitive thermal fringe, the short-run revenue function of the hydro monopolist is non-concave. This implies that even if the demand function is stationary, equilibrium prices may fluctuate through the year. For given capacities, both hydro and thermal producers are better off under such an outcome than under the competitive outcome with constant prices, while consumers are worse off. Prices may fluctuate through the year also in the long-run equilibrium where capacities are endogenous. In such an equilibrium the hydropower monopoly will get a lower profit than it would have gotten had it been a price taker.
Keywords: L12; L13; L94; Q25; 330; Electricity prices; Hydropower; Stromtarif; Wasserkraft; Wärmeenergie; Unvollkommener Markt; Monopol; Theorie